THE EFFECT OF HOSPITAL ACCREDITATION ON IMPROVING SERVICE QUALITY AND PATIENT SAFETY: A LITERATURE REVIEW - Sukarno (LP2IHKI UMSurabaya, 2025)
Objective: To identify the effect of hospital accredition on improving service quality and patient safety. Methods: This journal uses a literature review methodology, using articles from PubMed and Google Scholar databases related to hospital accreditation. The journal criteria used were journals published in the last 15 years, namely 2009-2024. Results: In general, several journals explain that accreditation has a positive effect on service quality and patient safety. The quality of health services is very important for the overall quality of health. The quality of health services is reflected in its form, appearance, performance, function, and aesthetics. However, it is still necessary to conduct regular evaluations and the role of all hospital staff so that the quality of health is still achieved. Conclusion: Hospital accreditation has a significant impact on service quality and patient safety so that health quality will be maintained. Periodic assessments are carried out because the quality of service is not only influenced by accreditation but also by several other variables, which require a plan to maintain or improve the level of health care performance.